2016
DOI: 10.1111/echo.13236
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Valve Disease and Vascular Mechanics: Two‐Dimensional Speckle Tracking Echocardiographic Analysis

Abstract: Purpose: Degenerative aortic valve disease (AVD) is a complex disorder that goes beyond valve itself, also undermining aortic wall. We aimed to assess the ascending aortic mechanics with two-dimensional speckle tracking echocardiography (2DSTE) in patients with aortic regurgitation (AR) and hypothesized a relationship with degree of AR. Aortic mechanics were then compared with those of similarly studied healthy controls and patients with aortic stenosis (AS); finally, we aimed to assess the prognostic signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…CS of patients with aortic stenosis is lower than the patients with aortic regurgitation, but they are all lower than the healthy people. Interestingly, the survival rate of patients with baseline CS rate >0.88/s was significantly higher 59 . Moreover, the bicuspid aortic valve is also associated with aortic disease.…”
Section: Biomechanics Of Different Aortic Diseasesmentioning
confidence: 95%
See 1 more Smart Citation
“…CS of patients with aortic stenosis is lower than the patients with aortic regurgitation, but they are all lower than the healthy people. Interestingly, the survival rate of patients with baseline CS rate >0.88/s was significantly higher 59 . Moreover, the bicuspid aortic valve is also associated with aortic disease.…”
Section: Biomechanics Of Different Aortic Diseasesmentioning
confidence: 95%
“…Interestingly, the survival rate of patients with baseline CS rate >0.88/s was significantly higher. 59 Moreover, the bicuspid aortic valve is also associated with aortic disease.…”
Section: Other Cardiac Diseases Affecting the Aortamentioning
confidence: 99%
“…The sum of the outflow tract obstruction due to the calcified aortic valve leaflets and the reduced arterial compliance result in an increasing valvulo-arterial impedance, which in turn represents the factor opposing to ventricular ejection by absorbing the mechanical energy developed by the heart [ 4 ]. Several studies have also demonstrated that AS is linked to a stiff dilated aorta [ 5 , 6 ], as assessed by aortic stiffness with either clinical imaging tools [ 7 ] or computational models [ 8 , 9 , 10 ]. To supply the increased requirement of energy, the heart changes his shape and function and this process is well known as cardiac remodeling [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Speckle-tracking echocardiography (STE) has emerged as a reliable measurer of left ventricle (LV) 6 systolic function 23 due to its fast, accurate, angle-independent and offline processing of myocardial deformation. 24,25 It has already been proved as an important initial predictor of LV dysfunction in aortic valve diseases through the measurement of global longitudinal strain (GLS). 26 Since 2008, STE has also been used to evaluate vascular wall properties of proximal elastic arteries.…”
Section: Introductionmentioning
confidence: 99%
“…26 Since 2008, STE has also been used to evaluate vascular wall properties of proximal elastic arteries. 25,27 It assesses the circumferential and longitudinal deformation that an artery undergoes during the cardiac cycle. Its values, in particular circumferential ascending aortic strain and its rate, have been described as important complementary parameters to the classic echocardiographic evaluation of patients with aortic stenosis.…”
Section: Introductionmentioning
confidence: 99%